THE ANALYSIS OF TRANSLATION TECHNIQUES OF ARCHITECTURAL TERMS FOUND IN MODERN INTERIOR DESIGN - Putu Devi Maharani; Ni Made Verayanti Utami (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTThis paper entitled The Analysis of Translation Techniques of Architectural Terms Found inModern Interior Design is mainly aimed at identifying the translation techniques used by the translator totranslate the architectural terms and is also aimed at analyzing the constituent structure of the architecturalterms in the target language. The data focused on the translation of architectural terms found in the bilingualbook of interior design compilations entitled Modern Interior Design. In the early stages of observation hasfound there are some different structure of phrase that used in architectural term from the source languagethat used by the translator to make them acceptable in target language. So this research tried to identify howthe different structure of both source and target language to describe architectural term to be accepted intranslation as the technique of the translation process. Moreover the translation technique that used by thetranslator analyzed to find out why that be acceptable in target language. The method of collecting the datain this research used direct observation method. The bilingual book of Modern Interior Design read. Then,the sentences that represent the architectural terms chose. After the data collected, they analyzed. The dataanalyzed is the results of the research. There are two main theories used in analyzing the data; the theoryof translation technique is proposed by Molina ad Albir (2002) and supporting theory from Brown & JimMiller (1990) about constituent structure to compare the structure of source language and target language.Keywords: translation technique, architectural term, constituent structureABSTRAKPenelitian bertujuan untuk mengidentifikasi teknik terjemahan yang digunakan oleh penerjemah untukmenerjemahkan istilah arsitektur dan juga bertujuan untuk menganalisis struktur konstituen istilaharsitektur dalam bahasa target. Data berfokus pada terjemahan istilah arsitektur yang ditemukan dalambuku dwibahasa kompilasi desain interior berjudul Desain Interior Modern. Pada tahap awal pengamatantelah ditemukan ada beberapa struktur frasa berbeda yang digunakan dalam istilah arsitektur dari bahasasumber yang digunakan oleh penerjemah untuk membuatnya diterima dalam bahasa target. Makapenelitian ini mencoba mengidentifikasi bagaimana perbedaan struktur baik bahasa sumber maupunbahasa target untuk menggambarkan istilah arsitektural yang dapat diterima dalam penerjemahan sebagaiteknik proses penerjemahan. Selain itu teknik penerjemahan yang digunakan oleh penerjemah dianalisisuntuk mencari tahu mengapa itu dapat diterima dalam bahasa target. Metode pengumpulan data dalampenelitian ini menggunakan metode observasi langsung. Buku bilingual dari Desain Interior Moderndibaca. Kemudian, kalimat yang mewakili istilah arsitektur dipilih. Setelah data terkumpul, merekamenganalisa. Data yang dianalisis adalah hasil penelitian. Ada dua teori utama yang digunakan dalammenganalisis data; teori teknik penerjemahan dikemukakan oleh Molina ad Albir (2002) dan teori pendukung dari Brown & Jim Miller (1990) tentang struktur penyusun untuk membandingkan strukturbahasa sumber dan bahasa target.Kata kunci: teknik terjemahan, istilah arsitektur, struktur bahasa